Peran Sikap Kewirausahaan dalam Memoderasi Pengetahuan Kewirausahaan dan Dukungan Keluarga terhadap Minat Berwirausaha - Rahmawati, Andriany; Rahman, M Fathur (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2024)
Entrepreneurial interest is a person's tendency or desire to start and develop a business. Entrepreneurship is important for vocational students in determining career alternatives. This study aims to examine the effect of entrepreneurial attitudes in moderating entrepreneurial knowledge and family support on entrepreneurial interest. The quantitative approach is the type of research used in this study, while the design used is a causality research design. The population in this study were 216 students of class XI and XII marketing majors SMK Negeri 2 Semarang. The sampling technique was proportional random sampling and obtained a sample of 139 students. Data collection tools using questionnaires. Data analysis techniques used in this study are descriptive statistics and SEM-PLS analysis (Structural Equation Modeling-Partial Least Square). The results of hypothesis testing suggest that: there is a positive and significant effect of entrepreneurial knowledge on entrepreneurial interest (34.3%), there is a positive and significant effect of family support on entrepreneurial interest (55.1%), there is a negative and significant effect of entrepreneurial attitudes in moderating entrepreneurial knowledge on entrepreneurial interest (41.8%), and there is a positive and significant effect of entrepreneurial attitudes in moderating family support on entrepreneurial interest (13.3%). This study found that entrepreneurial knowledge has a positive and significant effect on entrepreneurial interest; family support has a positive and significant effect on entrepreneurial interest; and entrepreneurial attitudes have a negative and significant effect on moderating entrepreneurial knowledge on entrepreneurial interest. This study recommends improved educational facilities, better entrepreneurship lessons, improved entrepreneurial attitudes, and family support to encourage students' interest in entrepreneurship.